(untitled) (Psico, 2006)
Magda Dimenstein Emanoel Batista de Lima Andreína Moura Monique Brito Rayanne Cardoso Vanessa Medeiros Universidade Federal do Rio Grande do Norte (UFRN) Objetivamos mapear bases de apoio familiares e comunitárias para adolescentes e jovens em Natal. Aplicamos um questionário em157 sujeitos de 13 a 24 anos, estudantes de escolas públicas. Constatamos que a violência, inclusive a doméstica, faz parte do cotidiano desses jovens: dos 157 estudantes, 124 já sofreram algum dano, seja ele físico ou moral. Aproximadamente 30% não buscaram qualquer tipo de ajuda. São escassos os espaços de lazer e programas para jovens, visto que apenas 50% deles conhecem algum grupo ou pessoa que desenvolve atividades culturais, esportivas ou de lazer na comunidade. Observamos que os sujeitos recorrem com mais freqüência às bases de apoio informais indicando que as bases formais não se configuram como dispositivos de suporte social. A busca das bases informais aponta que as relações estabelecidas informalmente no espaço da rua têm mais ressonância, configurando-se como um lugar importante no qual há troca de valores e de afetos. Palavras-chaves: Bases de apoio; crianças; adolescentes; jovens; violência. ABSTRACT Family and community support as a strategy to fight off violence We mapped the familiar and communitarian support bases for adolescents and young adults in Natal/RN. In order to accomplish that we applied a questionnaire to 157 students from public schools (aged 13 to 14) and observed the violence (including the domestic one) is a constant part of their daily routine: among all students interviewed, 124 have already suffered some kind of physical or moral damage. Approximately 30% of them never searched for any sort of help. The leisure opportunities and social programs for adolescents and young adults are quite scarce, for only 50% of them know some group or person who develop cultural, leisure or sport activities within the community. We observed the subjects more frequently search for help in informal social support bases, which demonstrates the formal ones are not considered to be sources of social support. The search for help in informal bases indicates the relations informally established on the streets have greater impact and, hence, those bases consist of an indispensable place in which there is great exchange of values and affection. Key words: Social supports; children; teenagers; young adults; violence.